New methods, old questions: advancing the study of unconscious perception - Jimenez, Mikel; Prieto, Antonio; Montoro, Pedro R.; Hinojosa, José Antonio; Kiefer, Markus (Frontiers in Psychology, 2025)
Since the early experimental studies of the late 19th century, research on unconscious perception has been shaped by persistent methodological challenges and evolving experimental approaches aimed at demonstrating perception without awareness. In this review, we will discuss some of the most relevant challenges researchers have faced in demonstrating unconscious perception, and examine how different measures of awareness (e.g., objective vs. subjective) yield different awareness thresholds—often leading to two alternative approaches to demonstrating unconscious perception. We will further explore new methodologies in the field, such as regression-based Bayesian modeling, sensitivity vs. awareness (SvA) curves derived from General Recognition Theory (GRT), the liminal-prime paradigm, and two-interval forced choice (2IFC) designs. Finally, we emphasize the need for brain-based approaches to unconscious perception and discussed some promising studies in this area, while also highlighting the role of individual differences and alternative frameworks such as predictive coding and active inference views in future research. Overall, the new approaches and methodologies discussed here will advance the field by addressing the challenges inherent in demonstrating cognition in the absence of awareness.